Mewujudkan Masyarakat Hijau Pusat Komuniti Desa, Pekan Nenas Pontian, Johor Bahru, Malaysia Melalui Pelatihan Pemanfaatan Minyak Jelantah sebagai Bahan Pembuatan Sabun Batang: Creating a Green Community Village Community Center, Pekan Nenas Pontian, Johor Bahru, Malaysia Through Training on the Use of Used Cooking Oil as an Ingredient for Making Bar Soap - Rahayu, Sri; Yusuf, Ade La; Nabila, Dasilva Azka; Kaulika, Siska Aprilia; Delina, Mutia; Kardiman, Yuyus; Khamis, Noorzana Binti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Repeated use of cooking oil produces waste in the form of waste cooking oil. Apart from being dangerous for health, waste cooking oil is also dangerous for the environment. To overcome this, waste cooking oil might be used for other harmless side products such as soap. To meet the soap standard, the waste oil must be reprocessed. Training on making soap from waste cooking oil has never been carried out before in the Pekan Nenas Pontian, Johor Bahru, Malaysia, so this service activity focuses on introducing, training, and implementing bar soap making from waste cooking oil to the community in the Pekan Nenas Pontian, Johor Bahru, Malaysia, as an effort to reduce waste cooking oil. The counseling webinar was held boldly on June 24, 2023. Meanwhile, soap-making training was held at Pekan Nenas Pontian on August 5, 2023. Soap quality testing was conducted at the Biochemistry Laboratory, State University of Jakarta, in September 2023. This activity used the active participation strategy method. The data obtained is in the form of social data, namely pre-test and post-test results, and scientific data in the form of soap quality tests, which are compared with the Indonesian National Standard (SNI) for solid soap, including pH tests, water content tests, foam height, and stability tests. Community knowledge has increased, as shown by the post-test score having an average of more than 60, namely 75, and the highest score is 90. This community service activity was a success.